Diálogo teológico con el pensar teocéntrico y trinitario de Ricardo Ferrara - Galli, Carlos María (Sapientia, 2022)
Ferrara was one of the theologians who, from the southernmost regions, contributed to placing the mystery of God at the center of theological attention. The author seeks to understand the key aspects of his theology through the examination of his treatise "De Deo" published in the work "The Mystery of God" and numerous other scattered texts. To do so, the focus is placed on the analogical correspondences between God – known in the theological realm of Christian wisdom – the metaphysical Principle on the philosophical plane, and the salvific Ultimate in the religious sphere. Building upon this paradoxical harmony, Ferrara's conception of the mystery of God the Father, Son, and Holy Spirit is expounded. In all these subjects, the author presents Ferrara's thoughts and endeavors to engage in dialogue with him and his interlocutors.